A baited remote underwater video survey of the Goukamma Marine Protected Area's ichthyofauna and a subsequent community structure comparison with the Betty's Bay, Stilbaai, and Tsitsikamma Marine Protected Areas - Dando, Jackson Willy (Department of Biological Sciences, 2020)
The Goukamma Marine Protected Area (GMPA) along the South African south coast has been in existence since 1990. The MPA encompasses 40.2 km2 of subtidal ocean, 76% of which is made up of sandy substrata and the remainder of which is made of rocky reefs. The imbalance in protected habitat type ratios prompted a proposal for an extension of the MPA's seaward boundary, referred to as the new no-take zone (NNTZ), and a restructuring of its eastern boundary, referred to as the new exploited zone (NEZ). The proposed boundary changes would increase the amount of protected reef by 53% and the overall size of the MPA by 38%. Goukamma has been surveyed using controlled angling surveys (CAS) and underwater visual census (UVC) but has yet to be surveyed using baited remote underwater video (BRUV). I collected and analysed mono-BRUV data over five years to determine patterns in fish community structure in Goukamma and compare it to the pre-existing CAS and UVC data. BRUVs are less invasive and more robust than the other two survey methods and have the potential to become the predominant method of surveying ichthyofaunal communities in South Africa. This work is therefore also intended as a baseline BRUV survey. BRUVs were deployed in Goukamma from 2013 to 2017. The survey produced 328 successful deployment records between 5-41.5 m across reef and sand sites. Date, site coordinates, depth, habitat type, protection zone were used as variables to explain patterns in the fish community data. Fish abundances were recorded using the MaxN metric. MaxN counts were recorded at the instance when the highest number of individuals of each species were present in a single video frame. The deployment records were converted into a single data frame and analysed using the RStudio integrated design environment. Ariids, scyliorhinids, serranids, sparids, and triakids were the most well represented ichthyofaunal families in Goukamma. Boopsoidea inornata, Cheimerius nufar, Chrysoblephus laticeps, Galeichthys feliceps, Mustelus mustelus, Pachymetopon aeneum, Poroderma africanum, Poroderma pantherinum, and Spondyliosoma emarginatum were the most frequently observed species throughout the MPA. Habitat type was identified as the primary determinant of diversity and abundance in the GMPA using multifactor analysis of variance (ANOVA) tests (species richness: F = 191.155, P < 0.001; relative abundance: F = 96.111, P < 0.001) and Wil coxon signed rank tests (Shannon-Wiener: W = 21 102, P < 0.001; Simpson: W = 18 553, P = 4.85x10-10). The reef sites supported a higher species richness and abundance than sandy sites throughout the MPA (Tukey: q = -4.41, P < 0.001 and q = -2.12, P < 0.001, respectively). Diversity and abundance were correlated with each protection zone's predominant habitat type. Exploited zones had significantly higher diversity and abundance than protected zones as a result of the imbalance in Goukamma's protected habitat type ratio (species richness: F = 27.740, P = 7.65x10-16; abundance: F = 10.438, P = 1.51x10-6 ; Shannon-Wiener: W = 17 314, P = 4.58x10-6 ; Simpson: W = 15 896, P = 3.42x10-3 ). The NNTZ had significantly higher species richness and abundance than the NEZ (Tukey: q = 3.07, P < 0.001 and Tukey: q = 1.48, P < 0.001, respectively). The proposed changes will therefore substantially boost diversity and abundance of protected fishes in Goukamma. BRUV samples in Goukamma recorded an overall higher species richness and abundance of sparids, chondrichthyans, and other reef-associated species than CAS and UVC samples. Over 90% more chondrichthyans were recorded in the BRUV samples than by the other two methods. BRUVs are therefore considered to be a suitable replacement for CAS and UVC surveys for the monitoring of South Africa's shallow subtidal ichthyofauna. BRUV data from Betty's Bay, Stilbaai, and Tsitsikamma were available for comparison with the Goukamma data, allowing for an extensive analysis of the south coast's ichthyofaunal communities. A combined data frame of 466 successful BRUV deployments from the four study areas was created. Multi-factor ANOVA tests indicated that location (F = 27.1, P = 1.00x103 ), depth zone (F = 17.4, P = 1.00x103 ), protection status (F = 23.1, P = 1.00x103 ), and habitat type (F = 91.8, P = 1.00x103 ) were all significant in determining community structure among the study areas. Reef sites had higher species richness and abundance than sand sites and species richness and abundance decreased from east to west along the south coast according to subtropical subtraction. However, the presence of an additional habitat type in Betty's Bay, namely kelp forests, resulted in it having a higher species richness and abundance than Stilbaai to the east. Betty's Bay's community structure was the least similar to the other three study areas as a result of the localised kelp forests in and around the MPA. These kelp forests shifted Betty's Bay's community structure away from the sparid-dominance observed in Stilbaai, Goukamma, and Tsitsikamma and towards a carangid- and scyliorhinid-dominance. However, cold-water associated sparids such as Pterogymnus laniarius were more abundant in Betty's Bay than the other study areas. Almost 80% of the species recorded among the study areas were represented in two or more of the four MPAs, indicating a good degree of redundancy of protection along the south coast within the depth ranges sampled. These data suggest that the Cape south coast is adequately protected from the perspective of fish representation. Review of the De Hoop, Sardinia Bay, and Bird Island MPAs should be conducted to further examine complementarity and redundancy of protection along South Africa's south coast.